The Extraction and Validation of Low-Frequency Wind-Generated Noise Source Levels in the Chukchi Plateau - Zhicheng Li; Yanming Yang; Hongtao Wen; Hongtao Zhou; Hailin Ruan; Yu Zhang (Journal of Marine Science and Engineering)
Low-frequency ocean noise (50–500 Hz) was recorded by a single omnidirectional hydrophone in the open waters of the Chukchi Plateau from 31 August 2021 to 6 September 2021 (local time). After other non-wind interference was filtered out, wind-generated noise source levels (NSLs) were extracted from the wind-generated noise. The correlation coefficients between the one-third octave wind-generated NSLs and sea surface wind speed exceed 0.84, an improvement of approximately 10% compared to those between the raw data and the wind speed. For 200–500 Hz, the wind-generated NSLs are highly consistent with Wilson’s (1983) estimated curve. The 50–300 Hz results closely match those of Chapman and Cornish (1993) from vertical line array (VLA) measurements. Both demonstrate the feasibility of extracting wind-generated NSLs by utilizing a single omnidirectional hydrophone in the Chukchi Plateau’s open waters. Furthermore, the research results of wind speed dependence and frequency dependence can be applied to calculate wind-generated NSLs in the Chukchi Plateau. Wind-derived ocean ambient noise data are useful for background correction in underwater target detection, recognition, tracking, and positioning.